Impact of reducing the threshold for acetylcysteine treatment in acute paracetamol poisoning: The recent United Kingdom experience. (September 2014) - Bateman, D. N.; Dear, J. W.; Carroll, R.; Pettie, J.; Yamamoto, T.; Elamin, M. E. M. O.; Peart, L.; Dow, M.; Coyle, J.; Gray, A.; Dargan, P. I.; Wood, D. M.; et al.
Abstract: Background. On 3 September 2012, the licensed indication for acetylcysteine was changed in the United Kingdom (UK) so that all patients with a plasma paracetamol concentration above a "100 mg/L" (4 h post ingestion) nomogram treatment line after an acute paracetamol (acetaminophen) overdose should be treated. This is a lower threshold than that used in the United States, Canada, Australia, and New Zealand. Here we report the impact of this change in the UK on the management of patients with acute overdose in different paracetamol concentration ranges. Methods. This is a cohort study, consisting of a retrospective analysis conducted on prospectively collected audit data in three UK hospitals. Following appropriate ethical and data protection authority approval, data for patients presenting within 24 h of an acute timed single paracetamol overdose were extracted. Numbers of admissions and use of antidote in relation to different paracetamol concentration bands (< 100 mg/L; 100–149 mg/L; 150–199 mg/L; and ≥ 200 mg/L at 4 h) were analyzed for one-year periods before and after the change. Results. Comparing the year before with the year after the change, there was no change in the numbers of patients presenting to hospital within 24 h of acute timed paracetamol overdose (1246 before and 1251 after), but more patients were admitted (759 before and 849 after) and treated with acetylcysteine (389 before and 539 after). Of the 150 additional patients treated with acetylcysteine in the year following the change, 114 (76%, 95% CI: 68.4–82.6) were in the 100–149 group and 9 (6.0%, 95% CI: 2.8–11.1) in the 150–199 group. Conclusions. Changes to national guidelines for managing paracetamol poisoning in the UK have increased the numbers of patients with acute overdose treated with acetylcysteine, with most additional treatments occurring in patients in the 100–149 mg/L dose range, a group at low risk of hepatotoxicity and higher risk of adverse reactions.